种蒽醌法生产过氧化氢工艺中循环工作液再生方法和种生产过氧化氢的方法 (2018)
本发明公开了种蒽醌法生产过氧化氢工艺中循环工作液再生方法，包括将循环工作液与第催化剂接触，得到过氧化氢含量降低的第接触液；将第接触液与第二催化剂接触，得到蒽酮型化合物含量降低的再生工作液。本发明还公开了种生产过氧化氢的方法，包括将萃取步骤得到的萃余液采用本发明的再生方法进行再生，得到再生工作液。采用本发明的方法对蒽醌法生产过氧化氢工艺过程中的循环工作液进行再生，能获得更高的蒽酮型化合物转化率，从而有效地降低循环工作液中蒽酮型化合物的累积含量，提高工作液的循环利用效率。 The invention discloses a regeneration method of circulating operating fluid in a production process of hydrogen peroxide by an anthraquinone method. The method comprises the following steps: the circulating operating fluid and a first catalyst are contacted, in order to obtain first contact liquid with reduced content of hydrogen peroxide; the first contact liquid and a second catalyst are contacted, in order to obtain regenerated operating fluid with reduced content of anthrone type compounds. The invention also discloses a method for producing hydrogen peroxide, and the method comprises the following steps: raffinate obtained in an extraction step is regenerated by the regeneration method, and the regenerated operating fluid is obtained. The circulating operating fluid in t